Modulation of plant growth and development through altered ethylene binding affinity of the ethylene receptor ETR1 - Sitwat Aman; Swadhin Swain; Esha Dutta; Safdar Abbas; Ning Li; Samina N. Shakeel; Brad M. Binder; G. Eric Schaller (BMC Plant Biology)
Abstract Arabidopsis senses ethylene through a five-member family of ethylene receptors, of which the ethylene receptor ETR1 plays the major role. We examined how changes in ethylene binding affinity of ETR1 can regulate physiological and molecular responses to ethylene, taking advantage of an Asp25Asn mutation that still produces a functional ETR1 receptor (ETR1D25N) but one with 100-fold reduced ethylene binding affinity compared to wild-type ETR1 (ETR1wt). Analysis was performed in a genetic background that lacks the five native members of the receptor family so that the specific role of ETR1 in plant growth and development could be assessed. From this analysis, we determined that changes in ethylene binding affinity of ETR1 are reflected in plant growth and responses to ethylene. Differences in plant growth and ethylene responses for the ETR1wt and ETR1D25N lines were uncovered in seedlings grown under light or dark conditions, and when assayed for short- or long-term responses to ethylene. Dose response analysis revealed that differences in the ethylene responses for ETR1wt and ETR1D25N lines are proportional to the binding affinity of the corresponding receptor variants. Results from the characterization of the ETR1wt line and an etr1 etr2 ein4 triple mutant demonstrate that plants have greater sensitivity to ethylene than previously recognized.